Islamic Crowdfunding: A Review Literature - Arzam, Arzam; Fauzi, Muhammad; Efendi, Faisal; Sulastri, Widia (Review of Islamic Economics and Finance, 2023)
Purpose – This study aims to review the current literature, both theoretical and empirical, which discusses Islamic Crowdfunding (ICF) and highlights future research directions.Methodology - This study is qualitative research, with the type being a literature review. The data search was carried out by searching the Emerald Publishing data base from the early 2016 – september 2023 period, using content analysis as a data analysis tool.Findings - During the period early 2016 – september 2023, 30 pieces of literature about ICF were detected in the Emerald Publishing data base. This literature is studied from various perspectives, such as studies in the perspective of sharia (Islamic law) / Sharia Complaint;, ICF is also studied from several sharia contracts (such as Mudharabah, Musyarakah Mutanaqisah, Salam, Murabahah, and Qard Hasan);, ICF is also studied from a donation perspective and as an alternative model for waqf institutions;, and ICF is also studied in the context of entrepreneurship, micro-enterprises, and small and medium enterprises (SMEs);. This research highlights that all the current literature contained in the data base paves the way for future research. However, this research looks at some of the ICF literature that is still little seen and could be a direction and challenge for future research, such as the Salam-based CF proposed by Saiti et al (2018) to apply to agricultural sector financing. Furthermore, recently, CF was proposed for housing finance, such as the model offered by Ma Md Taib (2023) and Ma et al (2023) who proposed a new housing affordability solution by combining the Islamic financial concept of Musyarakah Mutanaqisah with the cooperative and CF models.